PENGGUNAAN JOB STICK DALAM BERTANYA UNTUK MENGUPAYAKAN KEAKTIFAN MENJAWAB PERTANYAAN PADA SISWA KELAS II SD - Nofri Isabela Bano; Wiyun Philipus Tangkin (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
Active learning should involve students and teachers as a whole. However, the facts found were that students were passive and more silent. In this case, when asked, most of the students did not answer the teacher's question. This situation is repeated and only a few students are the same, who are always actively answering the teacher's questions. Therefore, the appropriate media can help students be more enthusiastic about participating in learning, one of which is a job stick. Thus, the purpose of writing is to describe the use of job sticks in asking questions, to seek activeness in answering questions for second-grade elementary school students, using descriptive qualitative methods. The results of this study are that after the job stick media was applied, most of the second-grade students were active in answering questions, enthusiastic, and enthusiastic, paying attention to every teacher's explanation, and all students had the same opportunity. In the application of the job stick, the teacher is enabled by God, to pursue the potential that God has given to students. It can be concluded that the use of job sticks in asking questions is able to seek activeness in answering questions in grade II elementary school students.